Big Data Challenges for e-Government Services in Nepal - Pradhan, Pratima; Shakya, Subarna (Journal of the Institute of Engineering, 2018)
With the digital disruption governments all over the world have envisaged into big data technology with the purpose of seeking values for the benefit of governmental activities. Governments have taken up this technology as a game changer of the e-governance. Citizen centric data over the web access and activities over the smart handsets have driven large volume of data not only in structured form but largely in unstructured form. The necessity of processing and analyzing the exploding data sets has driven governments to adopt this technology. This paper studies the possibility of digitalizing Nepal e-government services with innovative problem solving measures by adapting the Big Data applications. Following the global trend of digitalization and the ICT infrastructure development, Nepal e-Government services can initiate Big Data technology to resolve many of the governmental services. This paper explores some big data applications for the e-government of Nepal and further studies some challenges that Nepal could face while adopting the Big data in the e-government services. Journal of the Institute of Engineering, 2018, 14(1): 216-222